A Split-Mouth Study to Evaluate the Adjunctive Role of Guided Pocket Recolonization (GPR) to Non-Surgical Periodontal Therapy - Yasir Shahab Khan; Bikram Singh Brahma; Amitabh Srivastava; Vivek Srivastava; Shivam Yadav; Tanu Sahney (Journal of Pharmacy and Bioallied Sciences)
Background: The purpose of the study was to assess the effectiveness of prebiotic fructooligosaccharide (FOS) mixture and probiotic Saccharomyces boulardii (S. boulardii) when administered subgingivally as a supplement to scaling and root planing (SRP) in the treatment of chronic periodontitis. In addition, the N benzoyl DL arginine naphthylamide (BANA) test was used to examine the impact of probiotics on red complex organisms. Materials and Methods: Twenty systemically healthy participants with chronic periodontitis, with at least two periodontal pockets in each quadrant exhibiting probing depth (PD) ≥5 mm and clinical attachment level (CAL) ≥3 mm, participated in this split-mouth randomized controlled research. Two randomly chosen sites were chosen for each subject: one for testing, where SRP was followed by subgingival placement of the probiotic-prebiotic cocktail, and the other for control, where SRP alone was used. Assessments were conducted from baseline to 6 months later for the plaque index (PI), gingival index (GI), PD, and CAL. BANA was used to perform microbial assessments at baseline and at 1, 3, and 6 months. At certain intervals, the probiotic’s (S. boulardii) vitality was assessed both in vitro and in the pocket. Results: In both groups, there was a significant decrease in every clinical measure. A noteworthy enhancement was seen in the test group’s PI, GI, PPD, and CAL upon intergroup comparison in contrast to the control group. When comparing groups, it was shown that the test group’s BANA had significantly decreased after 3 and 6 months. While there was a significant difference and increase in in vitro vitality between the days, there was a significant difference and decrease in in vivo viability in the days that followed as compared to the day before. Conclusion: In comparison to SRP alone, subgingival administration of a probiotic-prebiotic mixture can be advantageous in non-surgical periodontal therapy for patients with chronic periodontitis and in managing the red complex organism’s recolonization over time.